Analisis Proses Kreatif Film Laskar Pelangi dan Efek Multiplier Pada Pariwisata Provinsi Bangka Belitung - Yohanes Mikha Boediarto (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
Film-induced tourism is an approach to filmmaking that connects the creative process with aspects of natural beauty/tourism objects. One film that implements this concept is the film Laskar Pelangi (2008). This study wants to analyze the creative process of making the film Laskar Pelangi (2008) and its multiplier impact on the economy, especially the tourism sector in Bangka Belitung Province. The analysis was carried out using a descriptive and literature study based on value chains in the creative industries, film-induced tourism and the theory of the multiplier effect. The results of the study explain that with a creative process that combines input place, personality & performance, a film can significantly impact the tourism sector and have a multiplier effect on other economic aspects.